2021
DOI: 10.1021/acscatal.1c03639
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into CO2 Electroreduction on Ni2P: Understanding Its Selectivity toward Multicarbon Products

Abstract: Recently, nickel phosphides (Ni x P y ) have been reported to enable selective electrochemical formation of multicarbon products (C 3 and C 4 ) via the CO 2 reduction reaction (CO 2 RR); nevertheless, their activities remain low. In order to understand the roots of their high selectivity and low activity and to direct the design of more active Ni x P y -based CO 2 RR catalysts, we investigate the CO 2 RR mechanism on Ni 2 P using density functional theory (DFT) calculations. We reveal that the reaction proceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 91 publications
2
42
1
Order By: Relevance
“…Figure S7 details all the steps we considered and discuss next. To form ethylene glycol, methylglyoxal, and 2,3-furandiol, the reaction must undergo carbon−carbon coupling through formaldehyde, which was first proposed and experimentally verified in our previous work on Ni 2 P 40 and confirmed by DFT calculations by Rappe et al 64 Our GC-DFT calculations reveal that Fe 2 P can catalyze CO 2 RR via two possible pathways to form formaldehyde, but with very different energetics for the intermediates, as summarized in Figure 5.…”
Section: ■ Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Figure S7 details all the steps we considered and discuss next. To form ethylene glycol, methylglyoxal, and 2,3-furandiol, the reaction must undergo carbon−carbon coupling through formaldehyde, which was first proposed and experimentally verified in our previous work on Ni 2 P 40 and confirmed by DFT calculations by Rappe et al 64 Our GC-DFT calculations reveal that Fe 2 P can catalyze CO 2 RR via two possible pathways to form formaldehyde, but with very different energetics for the intermediates, as summarized in Figure 5.…”
Section: ■ Introductionsupporting
confidence: 73%
“…This reaction step is highly exergonic by 0.83− 0.96 eV, depending on the geometry of *H 2 CO, which can readily undergo carbon−carbon coupling with other formaldehyde molecules on nearby Fe sites to form C 2 and higher products, as illustrated in Figure 4. The carbon−carbon coupling step was previously shown to be energetically favorable on Ni 2 P, 64 although the calculations were performed using the computational hydrogen electrode (CHE) model and require further validation, for example by GC-DFT.…”
Section: ■ Introductionmentioning
confidence: 99%
“…270,271 6) To date, the most widely reported C 2+ -producing catalysts are based on Cu. However, some new materials, including Ni 2 P (FE C 2 +C 3 = 99%), 272 Ni 2 P/Ho 2 O 3 core/shell nanoparticles (FE (CH 3 ) 2 CO = 25.4%), 273 hexagonal cobalt nanosheet (FE CH 3 CHO = 60%), 274 nitrogen-doped mesoporous carbon (FE ethanol = 77%), 148 nitrogen-doped nanodiamond Environmental Science: Nano Critical review (FE CH 3 COO − = 91.8%), 275 B-and N-co-doped nanodiamond (FE ethanol = 93.2%), 276 and N-doped graphene quantum dots (FE ethanol = 31%), 277 have exhibited a high performance for the production of C 2+ . The C 2+ product distribution and production rate on non-copper materials are comparable to that obtained using copper-based electrocatalysts.…”
Section: Perspectivesmentioning
confidence: 99%
“…94,95 DFT studies have shown that C-C coupling on Ni2P via *HCOO self-condensation is exergonic due to the presence of many types of H-binding sites, which results in selectivity toward multicarbon products. 103 It may be intuitive to think that the many H-adsorption sites promote higher activity for HER; however, it instead provides facile hydrogenation of CO2 intermediates. This phenomenon demonstrates that the complexity of TMP surfaces can be used to our advantage when tuning reaction selectivity.…”
Section: The Role Of Adsorption Site Diversity In Reactions Beyond He...mentioning
confidence: 99%
“…83 Considering intermediates other than hydrogen is important in electrochemical CO2 reduction as well, where a common theory is that a binary surface can provide local hydride sources for CO2 hydrogenation (Figure 4). 93,103 Li et al demonstrated that AgP2 has an onset potential of -0.22 V vs RHE, over 0.3 V lower than that of Ag (-0.59 V vs RHE). They attribute this partially to the strong adsorption of H on phosphorus sites that can suppress HER and serve as a local hydride source for CO2 hydrogenation.…”
Section: The Role Of Adsorption Site Diversity In Reactions Beyond He...mentioning
confidence: 99%